Ondertekening fusieprotocol. Links: Van Leeuwen (CHU); midden Van Zeil (KVP), rechts: Hans de Boer (ARP) - Melo, José
Ondertekening fusieprotocol. Links: Van Leeuwen (CHU); midden Van Zeil (KVP), rechts: Hans de Boer (ARP).